A bidirectional high-frequency link inverter using center-tapped transformer - Ramli, Mohd. Zulkifli; Nge, Chee Lim; Toh, Leong Soon; Salam, Zainal (IEEE, 2004)

(untitled)
In this paper, a bidirectional high-frequency link inverter is proposed. The main feature of the inverter is that the electrical isolation is provided by a high frequency centertapped transformer. Furthermore, the sinusoidal Pulse Width Modulation method is modified so that the transformer can be utilized near to its full potential. As a result, the power switches count is reduced, and the eficiency increased. A 1kW prototype inverter is built and typical results are presented.